Cross-Cultural Counseling In Islamic Education: Paradigm, Contemporary Challenges, And Service Model Based On Multicultural Competence - Luthfia Atsira Jon (Education Research Center, 2025)
Cross-cultural counseling has emerged as a critical paradigm in modern counseling practice, particularly in addressing the psychological needs of diverse populations in the context of globalization. This study examines the concept, principles, and implementation of cross-cultural counseling within Islamic education settings in Indonesia. Using a qualitative approach with literature review methodology, this research explores how culture fundamentally shapes human cognition, emotion, and behavior, and analyzes contemporary cultural challenges including acculturation stress, stereotypes, discrimination, and value confusion resulting from rapid social change. The findings reveal that effective cross-cultural counseling requires three core competencies: cultural awareness (recognition of counselor's own biases), cultural knowledge (understanding client's cultural background), and cultural skills (ability to apply culturally appropriate interventions). Within the Islamic context, this study proposes an integrative model that combines multicultural counseling principles with Islamic values such as tazkiyah al-nafs, social justice (al-'adl), and respect for human dignity. The research identifies essential support services including culturally sensitive assessment, multicultural supervision, community collaboration, and spiritual-religious interventions. This study contributes to the development of culturally responsive counseling practices in Islamic educational institutions and provides a framework for counselors working with Muslim clients in multicultural settings.